PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) DENGAN PENDEKATAN BERDIFERENSIASI DALAM KURIKULUM MERDEKA TERHADAP KEMAMPUAN PEMAHAMAN MATEMATIS SISWA SMA - Wulan Citra Sari; Hartono; Utin Desy Susiaty (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to find out how the application of the PBL and STAD models with a differentiated approach in the independent curriculum to the mathematical comprehension ability of high school students. The type of research used is an experimental method with a quantitative approach and a form of quasi-experimental design research, while the research used is a post test only control design. The population in this study is all students of grade XII of SMA Negeri 3 Sungai Kakap which consists of 2 classes, namely class A and class B. The sampling technique used in this study is the Saturated Sampling technique, where all populations in this study are used as samples. The sample in this study is class A as a control class and class B as an experimental class. Based on the results of this study, it can be concluded that there is no difference between the PBL and STAD learning models with the differentiated approach of grade XII students of SMA Negeri 3 Sungai Kakap